PERAN GURU SEBAGAI APLIKATOR PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA BELAJAR - Setiyaningsih, Suci; Wiryanto, Wiryanto (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to identify and describe the teacher's role as an applicator of the Pancasila student profile in the Independent Learning Curriculum. This research uses a qualitative approach with a literature study design. The results of this study conclude that in realizing the Pancasila student profile in the curriculum which is a plan and arrangement that contains goals, content, materials and teaching methods must be highlighted can have a good impact on the implementation of Pancasila values focused on the teacher's role in the formation and personality of students carried out to support the profile of Pancasila students in the Independent Learning Curriculum in the following ways: First, provide advice which is a form of coaching to students so that they do not make mistakes. Second, the attitude of tolerance which is one of the characteristics of the nation's character that every human being must have. Third, strengthening discipline which plays a very important role to be implemented in the school environment in order to shape the character of students who are disciplined. Fourth, love for the homeland where there are many agendas carried out both in the school environment and in the community that will have a positive impact on the progress of the nation.